Effect of light, temeprature and competence in the gametophytic phase of two forest ferns: Athyrium filix-femina and Dryopteris affinis subsp. affinis - Pangua Fernández-Valdés, Emilia; Pajarón, Santiago (Botanica Complutensis, 2021)
Athyrium filix-femina and Dryopteris affinis subsp. affinis are forest ferns that live together frequently. Spore viability and speed in germination, together with gametophyte development are cues for the competitive success of ferns in a certain habitat. Monospecific and mixed spore cultures were established, and kept at 10º, 15º and 20 ºC, and at low light intensity, from 1.8 to 1.0 µmol m-2 s-1, the latter at 20 ºC. Total germination percentages and time (T50), were registered in each case. In addition, gametophyte development and sexual expression was studied in both species. Final germination percentages were generally high, slightly higher in cultures with mixed spores. However, temperature clearly affected germination time that was shorter in Dryopteris at all tested temperatures. Cultures at low light intensities rich high germination percentages, decreasing markedly at 1 µmol m-2 s-1, notably in Athyrium. Sexual expression in mixed cultures, on soil at 20 ºC and 50 µmol m-2 s-1, was similar after three and six months. Athyrium showed high percentages of female gametophytes promoting sporophytic outcrossing, while Dryopteris showed a high number of apogamous sporophytes.